Pomen stališč učencev do angleščine za pouk v heterogenih razredih - Klemen Blatnik, Nina (Revija za elementarno izobraževanje, 2022)
The article investigates the impact factors which influence pupils' attitudes towards learning English as a foreign language, since these represent an important source of information for planning lessons in heterogeneous or mixed ability classes. The empirical part presents the results of a study among third graders (n=90), aimed at identifying the impact of the following factors on their attitudes: the age at which they started learning English, their gender, the exposure to English in their home environment and the valuable others (teachers, parents, and peers). The results suggest that in this age group, parents and teachers have a more salient influence on the learners' attitudes towards English than their peers.
Keywords: angleščina kot tuji jezik.; English as a foreign language; foreign language attitudes; foreign language motivation; heterogeneous classes; heterogeni razredi; pomembni drugi; stališča do tujih jezikov; tujejezikovna motivacija; valuable others